PERKEMBANGAN ART TOYS PADA MASYARAKAT URBAN DI INDONESIA: SEBUAH TINJAUAN LITERATUR: DEVELOPMENT OF ART TOYS IN URBAN COMMUNITIES IN INDONESIA: A LITERATURE REVIEW - Muhammad Ghifari Prima Asli; Sangayu Ketut Laksemi Nilotama; Achmad Syarief (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
The presence of adults in urban communities who like toys slowly shifts the notion that toys are always associated with children. Various types of toys on the market, one of them is art toys, toys that have artistic value. In its growth, art toys, which are part of popular culture, also have an influence on the art and toy industries. This study aims to analyze the rise and growth of art toys in the world and Indonesia, as well as to discuss the growht of the art toys scene as works of art, industrial products and part of popular culture.  The method used in this research is qualitative with a descriptive approach by collecting and studying information from various sources. It is known that art toys are toys that have artistic value, as well as works of art in the form of toys that are heavily influenced by popular cultural products from other industries such as films, video games, comics, series, cartoons, music and others. Art toys also have their own market segmentation in the art and toy industries, even other industries such as fashion. This research is expected to be a reference and knowledge related to art toys as art objects.